Life cycle assessment of aluminium cans and glass bottles - Luque Calvo, Ana María; Cerrillo-González, María del Mar; Villén-Guzmán, María Dolores; Paz-García, Juan Manuel (My University, 2020)
In this work, we present a simplified LCA on two commom products: an aluminum can and a glass bottle, both containing the same amoung of beverage (1/3 L of beer). The work presented here seeks to find out which option would be less harmful to the environment by studying the CO2 emissions produced by each container using a combined the cradle-to-cradle and cradle-to-grave approach, based on the current recycling rates in Spain. The functional unit is set to 1 m3 of beer, and the target consumer is someone purchasing beer at a supermarket. Therefore, according to the current waste management system in Spain, glass bottles are considered not reusable: This means that they are either disposed to landfill or deposited to the glass container for recycling. Recycling of glass would involve using the glass as raw material to produced new bottles. The free to use database IDEMAT has been used in the work presented here to obtain the data necessary for the Life Cycle Inventory. The results indicate that purchasing beer in aluminiun cans have a lower environmental impact than non-reusable glass bottles. The main reason related to this results are the lower transport emissions related to the cans due to the lower weight. This means that, for the same amount of beer, the energy required to transport the bottles is higher than the cans, and therefore the CO2 emissions are also higher. Additionally, aluminium is 100% and infinitely recyclable, while glass bottles made of recycled glass still need a certain intake of new raw material (of around 40%). The results presented here do not contemplate the posiblity to clean and reuse the bottles, which is expected to have a lower environmental footprint that the two scenarios discussed here.
Keywords: Ciclo de vida del producto; Aluminio – Reciclado; Vidrio – Reciclado; Reciclado; Operaciones de reciclado (Tecnología química); Life cicle assessment; IDEMAT; Circular economy; Recycling